Incommensurately modulated structure of Zn4Si2O7(OH)2·H2O at high pressure - Roman Gajda; Wojciech Sławiński; Tomasz Poręba; Jan Parafiniuk; Mohamed Mezouar; Przemysław Dera; Krzysztof Woźniak (IUCrJ)
High-resolution single-crystal X-ray diffraction experiments on Zn4Si2O7(OH)2·H2O hemimorphite were conducted at high pressure using diamond anvil cells at several different synchrotron facilities (ESRF, Elettra, DESY). Experimental data confirmed the existence of a previously reported phase transition and revealed the exact nature of the incommensurate modulation. We report the incommensurately modulated structure described in the (3+1)D space group Pnn2(0, β, 0)000. We have determined the modulation mechanism, which involves the fluctuation of atoms between two main positions, occurring mainly along the [100] direction, perpendicular to the modulation vector. Moreover, our results reveal that the phase transition occurs at lower pressure than previously reported.